Evaluation of dried blood spots for hepatitis B and D serology and nucleic acid testing. Issue 2 (24th April 2019) - Jackson, Kathy; Holgate, Thomas; Tekoaua, Rosemary; Nicholson, Suellen; Littlejohn, Margaret; Locarnini, Stephen
Abstract: Areas with the highest burden of hepatitis B virus (HBV) infection are often low‐middle‐income countries with limited access to diagnosis due to isolation, affordability, and/or feasibility. Dried blood spots (DBSs) provide an alternative for remote areas where collection and transportation of serum is impractical. In this study, the application of DBS for serological and molecular detection of HBV and hepatitis D virus (HDV) was evaluated. Hepatitis B surface antigen was detected in 87 of 91 (95.6%) DBS. Seventeen of 21 (81%) had detectable HBeAg and 52 of 71 (73.2%) were anti‐HBe positive. Anti‐HD was detectable in 11 of 12 (91.6%) spiked control DBS after an initial failure to detect in patient DBS. HBV DNA was detected from 50 of 70 (71.4%) DBS with serum loads greater than 200 IU/mL in an in‐house assay and 18 of 24 (75%) DBS with loads exceeding 389 IU/mL in a commercial assay. Using linear regression, HBV DNA loads from DBS were able to predict serum loads in 46 of 50 (92%) samples to within 1 log of actual serum load. HDV RNA was detected in 42 of 47 (89%) DBS with serum levels greater than 7200 IU/mL. DBSs are recommended for diagnosis of HBV, monitoring, and detection of high loads in pregnant women where peripheral blood testing remains unfeasible. Detection of HDV RNA from DBS may prove useful in endemic areas.